Morphological aspects and distribution of granules composed of deproteinized bovine bone or human dentin into a putty mixture: an in vitro study - Pimentel, Inês (2023)
Objective: The main aim of this study was to evaluate the morphological aspects and distribution of granules composed of deproteinized bovine bone mineral (DBBM) and human dentin-derived bone graft (HDBG) into a putty consistency mixture. Materials and methods: DBBM or HDBG were mixed with an alginate-based hydrogel at two different granule/hydrogel ratio (1:1 and 1:3) and divided into four test groups while two control groups were composed of DBBM or HDBG free of hydrogel. Groups of specimens were cross-sectioned for morphological evaluation by scanning electron microscopy (SEM) at backscattered electrons mode. Details on the dimensions and pores’ size of DBBM and HDBG were evaluated after mixing different amounts of particles and alginate-based hydrogels. Results: Microscopic analyses revealed a size of DBBM granules ranging from 750 up to 1600 μm while HDBG particles showed particle size ranging from 375 up to 1500 μm. No statistical differences were identified regarding the size of granules (p > 0.5). The mean values of pores’ size of DBBM particles were noticed at around 400 μm while HDBG particles revealed micro-scale pores of around 1–3 μm promoted by the dentin tubules (p < 0.05). The lowest distance between particles was at 125 μm for HDBG and 250 μm for DBBM when the particle content was increased. On decreasing the particles’ content, the distance between particles was larger for DBBM (~ 1000 μm) and HDBG (~ 1100 μm). In fact, statistically significant differences were found when the content of granules increased (p < 0.05). Conclusions: The increased content of bioactive ceramic granules in a putty consistency mixture with hydrogel decreased the space among granules that can promote a high ceramic density and stimulate the bone growth over the healing process. Macro-scale pores on bovine bone mineral granules stimulate the formation of blood vessels and cell migration while the micro-scale pores of dentin-derived granules are proper for the adsorption of proteins and growth of osteogenic cells on the bone healing process. Clinical significance: A high amount of bioactive ceramic granules should be considered when mixing with hydrogels as a putty material since that result in small spaces among granules maintaining the bone volume over the bone healing process. Deproteinized bovine bone mineral granules have macro-scale pores providing an enhanced angiogenesis while dentin-derived granules possess only micro-scale pores for the adsorption of proteins and proliferation of osteogenic cells on the bone healing process. Further studies should evaluate the combination of different bioactive ceramic materials for enhanced bone healing.